Two phase sinusoidal pulse width modulation with remodulation in the "converter – electric motor system" - A. V. Saushev; I. V. Belousov; V. F. Samoseiko (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. Two-phase pulse width modulation in "the converter – electric motor" system is considered. It is noted that two-phase voltage modulation, which is implemented on a set of two electronically-key half bridges, ﬁnds important practical application. Restrictions are given on the values of the modulating functions of the potentials of the keys of the half-bridges, violation of which leads to intermodulation. Intermodulation leads to the appearance of low frequency harmonics in the composition of voltages and is the reason for a decrease in the energy eﬃciency of "the converter – electric motor" system.Goal. The aim is to study the eﬀect of re-modulation on the energy processes of two-phase pulse width modulation in "the converter – electric motor" system.Materials and methods. New modulating functions with constraints have been introduced to analyze the phenomena associated with modulation. Methods of analysis of electrical circuits were used in the work.Results and discussion. Quantitative estimates of the modulation and its relation to the modeling function are obtained. It is shown that the modulation makes it possible to increase the amplitude of the harmonic base. This has a positive eﬀect on the energy parameters of a single-phase bridge. However, the intermodulation leads to the appearance of low-frequency harmonics in the current spectrum. Dependences characterizing the degree of increase in current dispersion in the load during modulation, which is the main criterion for PWM quality, are obtained. Recommendations are given for the design of a bridge converter, taking into account the phenomenon of intermodulation.Conclusion. The results can be used in the development of algorithms for controlling frequency converters in frequency control systems of electric drives.